Theory and practice of excise taxation : smoking, drinking, gambling, polluting, and driving - Cnossen, Sijbren (Oxford ; New York : Oxford University Press, 2005)
This book is on excise taxes on smoking, drinking,gambling, polluting and driving.
Includes bibliographical references and index.
aia 2/5/13, ijb 19/03/2019
Loan
Keywords: Excise tax